Production priorities in dynamic relationships - Jean Guillaume Forand; Jan Zapal (Theoretical Economics, 2020)
We characterise optimal contracts in a dynamic principal-agent model of joint production in which project opportunities are heterogenous, utility from these projects is non-transferable and the agent has the option to quit the relationship at any time. In order to demand the production of projects that benefit her but not the agent, the principal must commit to produce projects that benefit the agent in the future. Production at all stages of the relationship is ordered by projects' cost-effectiveness, which is their efficiency in transferring utility between the principal and the agent: cost-effective demands impose relatively low costs on the agent, and cost-effective compensation imposes relatively low costs on the principal. Over time, optimal contracts become more generous towards the agent by adding commitments to less cost-effective compensation. In turn, because this new compensation cannot be profitably exchanged against less cost-effective demands, the principal narrows the scope of her demands.
Keywords: C73; D86; L24; 330; Dynamic contracts; incentive provision; heterogenous projects